2018
DOI: 10.1111/odi.12960
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation of lost teeth related to maintenance of cognitive function

Abstract: Our data showed that NRLT was independently associated with CI. Hence, rehabilitation of the lost teeth could be important for the maintenance of cognitive function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Low masticatory ability due to tooth loss had a negative effect on nutritional status [ 7 ]. Rehabilitation of lost teeth could reduce the risk of cognitive impairment because it could potentially increase the occlusal force [ 8 ]. These statistics outline that the dental problems could be related to occlusal force, which indicated that total occlusal force is important.…”
Section: Introductionmentioning
confidence: 99%
“…Low masticatory ability due to tooth loss had a negative effect on nutritional status [ 7 ]. Rehabilitation of lost teeth could reduce the risk of cognitive impairment because it could potentially increase the occlusal force [ 8 ]. These statistics outline that the dental problems could be related to occlusal force, which indicated that total occlusal force is important.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, contradicting findings between oral health and cognition could be attributed to the fact that most previous studies did not adjust their analyses for either dental rehabilitation or masticatory function. 11 The studies that addressed these oral health conditions evaluated the onset of dementia, and used a combination of baseline self-reported number of teeth and use of dentures as the oral health measures. [13][14][15][16] Yang et al reported a significant interaction of tooth loss and denture use with the onset of dementia.…”
Section: Discussionmentioning
confidence: 99%
“…9 Regarding cognitive impairment, cross-sectional studies evaluated the association between this condition and chewing ability, 10 and the number of teeth with or without the use of dental prostheses. 11 Limited findings are available from prospective cohort studies. After adjustment for covariates, two studies suggested no association between cognitive impairment with the use of dental prostheses and number of teeth, 12,13 whereas others reported a significant association with a lower risk of dementia among individuals wearing dentures.…”
Section: Introductionmentioning
confidence: 99%
“…Tooth loss due to periodontitis was determined using interviews by dentists. Established periodontitis was classified into two groups: No (healthy or stage I–II) and Yes (stage III–IV) [ 36 ].…”
Section: Methodsmentioning
confidence: 99%